Metal Ceramic, Namely Metal Composite Prosthesis, Viable Esthetic Alternatives to Contemporary Dentistry? - Earar Kamel; Diana Cerghizan; Mihaela Moisei; Madalina Matei (Romanian Society of Oral Rehabilitation, 2016)
Aim This study aims at an analysis of the clinical and technological aspects that decisively influence the clinical esthetic finality, as reflected in a representative number of clinical cases diagnosed with partially reduced edentation, the therapeutic choices being represented by metal ceramic, namely metal composite restorations. Material and Method: The factual material was represented by a number of 25 clinical cases diagnosed with partially reduced edentation, the therapeutic solutions being represented by metal ceramic, namely metal composite bridges, the analysis of the multiple factors that influence the technological algorithm of certain representative practical cases leading to pertinent conclusions regarding the individualization of the clinical technological algorithm. Results and Discussions :Out of the extremely large and diverse range of esthetic restorative materials, ceramic remains the "uncrowned queen of restorative materials", ensuring that sense of naturalness so much sought after by its translucent similarity to dental enamel. Conclusions:The particular conditions of the prosthetic field influence the clinical technological details of the treatment algorithm, its clinical finality being that of masking deficits or excesses, in full agreement with the corrective proprosthetic interventions